On Non-Existence of Wandering Domains of Entire Functions of Finite Order - Dr. Rajesh Kumar Sharma (International Journal of Advanced Science and Technology, 2020)
It is already known that wandering domains do not exist for rational functions whereas examples for existence of wandering domains of transcendental entire functions have already been constructed. In this paper, we prove results regarding non-existence of wandering domains using the spiser class S. We proved that wandering domains do not exist for a polynomial and an entire map f of finite order whose derivatives have finite number of zeros.